Price bubbles of new-technology IPOs - Haim Kedar-Levy (The Journal of Entrepreneurial Finance and Business Ventures, 2002)
Asset pricing models with atomistic agents typically relax assumptions concerning rationality and/or homogenous information in order to track endogenous bubbles. In this model, identically informed rational agents hold a Perceived Law of Motion (PLM) for a single new technology asset at IPO, yet they differ with respect to risk aversion. By mapping risk preferences to strategies, we use marginal supply and demand functions to solve for the PLM if REE holds. By relaxing the assumption of complete knowledge of agent's tastes and wealth, post-IPO bubbles emerge where the Actual Law of Motion is an amplification (bubble) of the price processes vs. the PLM.
Keywords: 650